Categories of (I,I)-Fuzzy Greedoids - Zhen-Yu Xiu; Fu-Gui Shi (Journal of Function Spaces)
The concepts of I-greedoids, fuzzifying greedoids, and (I,I)-fuzzy greedoids are introduced and feasibility preserving mappings between greedoids are defined. Then I-feasibility preserving mappings, fuzzifying feasibility preserving mappings, and (I,I)-fuzzy feasibility preserving mappings are given as generalizations of feasibility preserving mappings. We study the relations among greedoids, I-greedoids, fuzzifying greedoids, and (I,I)-fuzzy greedoids from a categorical point of view.